Application of steel bar bracings in renovation and modernization of historic buildings = Zastosowanie stalowych stężeń prętowych w renowacji i modernizacji obiektów zabytkowych - Kuchta, Krzysztof (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The use of steel bracings is possible in all four stages of engineering activities in the renovation and modernization of historic buildings, i. e.: protecting, repairing, strengthening and rebuilding. Steel bracings are auxiliary structural systems, which, due to their relatively small cross-section dimensions and low weight, provide an efficient way to achieve the required resistance and stability of the original historic building structural systems. The steel structure in most cases is the tissue that differs in style and material of genuine tissue which is present in a renewed historic building, but is also often a rational solution acceptable to the conservation and structural point of view.
Keywords: obiekty zabytkowe; stateczność ścian; stężenia stalowe; rekonstrukcja; przebudowa; historic building; steel bracing; renovation; reconstruction